Synthesis of para-aryl-substituted salicyldialdehydes - Reinhard, Dennis; Schöttner, Ludger; Brosius, Victor; Rominger, Frank; Mastalerz, Michael (European journal of organic chemistry, 2015)
Abstract para-Substituted salicyldialdehydes are versatile molecular building blocks for porous organic cages, fluorescent dyes, spirobenzopyrans, homooxacalixarenes, dinuclear metal complexes, macrocycles, and cryptands. To date, no procedures for the synthesis of para-aryl-substituted salicyldialdehydes have been reported, which would broaden the scope of the above-mentioned topics, especially in the field of sensors and dyes, because the aromatic π systems can be enlarged and absorption or fluorescent events can be fine-tuned by various substituents. Herein, two synthetic routes to para-aryl-substituted salicyldialdehydes with both electron-withdrawing and -donating aromatic units are reported.
Gesehen am 17.06.2020